-3y-10=8y+12

Simple and best practice solution for -3y-10=8y+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3y-10=8y+12 equation:


Simplifying
-3y + -10 = 8y + 12

Reorder the terms:
-10 + -3y = 8y + 12

Reorder the terms:
-10 + -3y = 12 + 8y

Solving
-10 + -3y = 12 + 8y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-8y' to each side of the equation.
-10 + -3y + -8y = 12 + 8y + -8y

Combine like terms: -3y + -8y = -11y
-10 + -11y = 12 + 8y + -8y

Combine like terms: 8y + -8y = 0
-10 + -11y = 12 + 0
-10 + -11y = 12

Add '10' to each side of the equation.
-10 + 10 + -11y = 12 + 10

Combine like terms: -10 + 10 = 0
0 + -11y = 12 + 10
-11y = 12 + 10

Combine like terms: 12 + 10 = 22
-11y = 22

Divide each side by '-11'.
y = -2

Simplifying
y = -2

See similar equations:

| 3/8÷1/6 | | (3/8)=(1/x) | | -2(7-n)+4=12 | | 16x=20x-13 | | -16x^2+48x+0=20 | | 2y(y^2)=128 | | 40x=39x+13 | | 240+30x=70x | | 4x=1x+3 | | (3/16)=(1/x) | | y^2-3x=-x^2 | | 4x^2+9+15x=0 | | 0.2(60)+0.05(12-x)=0.10(63) | | -4(3t-5)+9t=8y-9 | | -2(6x-8)+1=-12x+17 | | x8/x16 | | 0.19y+0.05(y+7000)=2510 | | d^4+2d^3-3d^2-4d+4=0 | | 2a(-2)+b=-4 | | R(x)=x*600-0.5x | | 5x+8=23-2x | | x^2=17x+60 | | -4.9x^2+14.7x+1=10.8 | | 10-3(a+2)=8+9 | | 20n^2-9n-20=0 | | 0.25-0.03(x+2)=0.02(3-x) | | 995=6x+x^2 | | 16x-8=.5(110+2x) | | 2x-43=64358 | | 3/9-5/9=2/9-8x/9 | | 18//.04 | | t^2-14t-22=0 |

Equations solver categories